Global Development Finance : the globalization of corporate finance in developing countries, 2007. - The World Bank (Washington, World Bank, 2007)
Global Development Finance (GDF), is the World Bank's annual review of recent trends in and prospects for financial flows to developing countries. It is an indispensable resource for governments, economists, investors, financial consultants, academics, bankers, and the entire development community. Vol I: Analysis and Outlook reviews recent trends in financial flows to developing countries. Vol II. Summary and Country Tables* includes comprehensive data for 138 countries, as well as summary data for regions and income groups. Also available on CD-ROM, with more than 200 historical time series.
Keywords: BUSINESS & ECONOMICS Public Finance; Debts, External; Debts, External Developing countries Statistics